Fluoride Content in Water Bodies Near Velliangiri Hills - B, SACHIN ADITYA; GANAPATHY, DR. DHANRAJ; SASANKA, DR. KEERTHI (The journal of contemporary issues in business and government, 2020)
Water is an essential natural resource for sustaining life. However, chemical composition has to be balanced in the available water to make it useful, in the current era of economic growth many natural and man made water bodies are getting polluted and becoming unfit for human use. Traces of fluorides are present in many waters; higher concentrations are often associated with underground sources. In areas rich in fluoride-containing minerals, well water may contain up to about 10 mg of fluoride per litre. The highest natural level reported is 2800 mg/litre.Many epidemiological studies of possible adverse effects of the long-term ingestion of fluoride via drinking-water have been carried out. These studies clearly establish that fluoride primarily produces effects on skeletal tissues (bones and teeth). Low concentrations provide protection against dental caries, especially in children. Fluoride being one of the most abundant anions present in naturally existing water bodies, its benefits or demerits in water depends on the amount/concentration, the results on comparing the samples from drinking water and collected river water the total dissolved salts concentration is almost double in collected water than that of drinking water,therefore it’s not completely safe for drinking. Thus the tested sample is unfit for drinking purposes.